ANALYSIS OF CHARACTER EDUCATION POLICY IMPLEMENTATION IN JUNIOR HIGH SCHOOLS MEDAN - Nurshabrina Hasan; Rosmala Dewi; Yuniarto Mudjisusatyo; Eka Daryanto (Institut Pendidikan Tapanuli Selatan, 2022)
The success of character education is part of the policy, program planning system and internal quality assurance. In practice, these policies often require further action to address the problem. The quality assurance of character education has not been able to be implemented optimally due to weak budget adequacy, not yet optimal practice of research and development, information systems, and teacher human resources. The aims of this study were to (1) describe and analyze the implementation of character education policies, (2) develop a hypothetical model of the internal quality assurance system for character education at SMP Riad Madani, SMP Baitul Aziz, and SMP Pusaka. The research method used is descriptive qualitative with case studies. Data were collected using purposive sampling technique and data were analyzed using constructionist analysis. The results of the study show that education policies are prepared based on the vision and goals of schools with different characteristics and programs. SMP Riad Madani prioritizes independence and personality, SMP Pusaka prioritizes tolerance, and SMP Baitul Aziz prioritizes religious values.